A Systematic Review of e-Service Learning in Higher Education - Bukas Marcus, Valerie; Azean Atan, Noor; Mohd Yusof, Sanitah; Tahir, Lokman (International Journal of Interactive Mobile Technologies (iJIM), 2020)
E-Service Learning is a service-learning course when the instruction and/or the service occurs online gains popularity among educators as we are transitioning to online learning platforms. The current study presents a systematic review of papers on the research involved information and communications technology (ICT) in the service-learning project. Studies have noted the growing use of ICT in service-learning projects for various purposes such as for communication and collaboration, data collection, reflection, and instruction delivery. However, very little research analysed students’ engagement in this e-Service Learning environment. Future research should be done to investigate an effective application of technology in service-learning courses, especially to attain the attention of digital natives nowadays and engaging learners instead of merely using technologies in service-learning courses.